A Review of Energy use and Carbon Footprint in Fishing with special reference to Life Cycle Assessment (LCA): Energy use and Carbon Footprint in Fishing - Jha, Paras Nath; Baiju, M. V.; Leela Edwin (Fishery Technology, 2025)
With over 4.1 million vessels operating worldwide the global fishing industry is critical for ensuring food security and supporting livelihoods. Asia leads in the total number of vessels globally with 2.68 million vessels which are operational, while India has about 0.166 million vessels (FAO, 2024). The fishing industry heavily depends on fossil fuels for fishing operations, which contributes significantly to greenhouse gas emissions. In 2011 alone, global fisheries consumed 40 billion litres of fuel, resulting in 179 million tonnes of CO2 emissions, which is about 4% of total emission from global food production (Parker et al., 2018). In Indian scenario fuel consumption and thus CO2 emissions per tonne of fish landed, have increased from 0.50 tonnes in 1961 to 1.52 tonnes in 2024. Mechanized and motorized vessels contributed the most to emissions, with trawlers emitting up to 1.43 tonnes of CO2 per tonne of fish. The economic challenges posed by rising fuel prices and inefficiencies in operations are highlighted in many fisheries, including India, where high fuel consumption and associated costs limits capacity utilization by up to 55% in many cases. This review examines strategies used for reducing energy use and emissions in fisheries and explores best strategies to minimize emissions from fishing fleet. Innovations in vessel design, fuel-efficient engines, and advanced gear technologies can be effective solutions for reducing energy use and emissions. Additionally, practices such as conducting energy audits, optimizing routes, and transitioning to alternative fuels like LNG and biogas can significantly improve sustainability. While traditional approaches based on fuel consumption provide a comparative understanding of energy use, Life Cycle Assessment (LCA) frameworks offer deeper insights into environmental impacts, making them valuable for shaping policies and practices that promote both economic and environmental sustainability in the fisheries sector.